A Qualitative Case Study on Overcrowding And Recidivism in The Banyuasin Regency Correctional Institution - Mayreista, Dita; Hanif, Alif Adin Adni (Al-Risalah, 2026)
This study contributes to analyze the strategies for the rehabilitation of prisoners implemented at the Banyuasin District Correctional Facility, with a primary focus on the issues of overcrowding and high recidivism rates. The rehabilitation process at the Banyuasin Correctional Facility faces significant challenges, such as overcrowding, which limits prisoners' access to optimal rehabilitation programs. Additionally, the high recidivism rate remains a serious concern, with approximately 30% of released prisoners re-offending. This research uses a qualitative approach with a case study conducted at the Banyuasin Correctional Facility. Data was collected through interviews with prisoners, correctional staff, and direct observations in the field. The findings indicate that despite efforts to improve the quality of rehabilitation, overcrowding and limited facilities continue to be major obstacles. Furthermore, the implemented educational and vocational training programs have proven effective in helping prisoners acquire life skills that can be used after their release. However, there are still challenges related to the lack of instructors and adequate facilities. The study also identifies that personality development programs, through religious activities and psychological counseling, play a crucial role in reducing recidivism. However, there is a need for stronger post-release support and collaboration with the private sector and educational institutions to enrich the curriculum and enhance the relevance of rehabilitation programs to the labor market. The results of this study are expected to contribute to formulating more effective rehabilitation policies at the Banyuasin Correctional Facility and provide insights for other correctional institutions in Indonesia in addressing overcrowding and recidivism issues.